THE ROLE OF STUDENTS' PSYCHOLOGICAL EXPLORATION IN CONTEMPORARY LITERATURE: A STUDY OF IAN MCEWAN AND JULIAN BARNES - Sudrajad, Wahyu (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
This study explores the psychological themes of memory, guilt, and identity in Ian McEwan’s Atonement and Julian Barnes’ The Sense of an Ending. Both novels delve into the malleability and unreliability of memory, examining how personal biases, emotional turmoil, and guilt distort characters' recollections of the past, thus shaping their identities. Through the characters of Briony Tallis and Tony Webster, the novels illustrate the profound psychological impacts of self-deception, regret, and the ongoing process of reconciling one’s past with their present self. This research analyzes how memory and guilt influence the characters’ actions and relationships, revealing that identity is not fixed but is instead an evolving narrative influenced by emotional and psychological revelations. By examining these themes, the study also highlights how contemporary literature can provide students with opportunities for psychological exploration and self-reflection.